(3GdGSJHUGQ aj eG GNJda ef GdCNHGQs - (3GdWhSj, CHh LYaQ, eMeO Hf GdMSf Hf Ydj, J (B460(3g`s ((3LYaQ Hf Ydj Hf LYaQ GdeTgOjs)
(3ChdgG (B:s
(3GdMeO ddg hdj GdMeO heSJMbg(B... (3CeG HYO aEfj QCjJ LeGYI ef ef CUMGHfG deG fXQhG aj cJGHfG GdcHjQ GdehShe HJgPjH GdCMcGe(B....s
(3BNQgG (B:s
(3HGH ef CMb HGdUdGI Ydi GdeQCI(B... (3aj gPjf GdNHQjf VQH ef(B...(3Je cJGH GdLRA GdChd ef GdGSJHUGQ(B...s
(3ebGHdI Ydi fSNI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B84s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B72s
(3EjVGM Gdecfhf(B: (3L(B2(3, U(B266s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs